A new family of Drosophila balancer chromosomes with a w- dfd-GMR yellow fluorescent protein marker. - Le, T.; Liang, Z.; Patel, H.; Yu, M.H.; Sivasubramaniam, G.; Slovitt, M.; Tanentzapf, G.; Mohanty, N.; Paul, S.M.; Wu, V.M.; Beitel, G.J. (Genetics, 2006)
We report new w- fluorescent balancers scorable from stage 13 through adulthood that bear a nuclear-localized yellow fluorescent protein marker directly driven by dfd and GMR enhancer elements. The utility of this marker is enhanced by identification of an anti-GFP/yellow fluorescent protein (YFP) serum that is compatible with heat fixation.